Apochrysinae (Neuroptera: Chrysopidae): New Larval Description and Subfamilial Comparisons - Tauber, Catherine A. (Zootaxa, 2014)
Although Apochrysinae is considered an important, ancient clade of Chrysopidae, its immature stages are very poorly known. Larvae are rarely seen, and descriptions are limited to the third instar of only one species in the genus Apochrysa. Herein, the larvae (all instars) of a second species, Apochrysa voeltzkowi (Weele), are described, and the features of the two Apochrysa species are compared with those of other chrysopids. The results provide support (one potential synapomorphy) for a phylogenetic relationship between Apochrysinae and Nothochrysinae and additional support for two synapomorphies previously proposed for Nothochrysinae. Diagnostic larval characteristics are proposed for the genus Apochrysa, and species-specific features are identified for the two known Apochrysa larvae.